The Trend of Mixed Methods Research Employed in the Journal of NELTA (2009-2022) - Bidari, Samikshya; Gnawali, Laxman (Journal of NELTA, 2023)
This research trend analysis aims to understand the prevalence of Mixed Methods Research (MMR) in English language teaching (ELT) research within the Journal of NELTA from 2009 to 2021, identifying the extent to which MMR is employed in the ELT field and assessing adherence to the International Journal of Mixed Methods Research (IJMMR, 2018) guidelines. A two-stage screening process was conducted, initially involving the manual screening of 176 articles and subsequently assessing 20 shortlisted articles against the checklist of IJMMR. The analysis confirms a limited utilization of MMR in ELT research, with only 20 (approximately 11%) of the 176 reviewed articles incorporating MMR, while qualitative and quantitative methodologies take precedence. Adherence to the International Community of Practice guidelines, as established by IJMMR, is lacking in most articles, emphasizing the need for better alignment with established guidelines to enhance MMR quality in ELT research. This study highlights a substantial gap in the adoption of MMR in ELT research, possibly due to methodological conservatism and a lack of awareness and training within the ELT community, presenting an opportunity for scholars to explore MMR’s potential to bridge gaps in traditional ELT research and enhance the understanding of language teaching and learning processes.